GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN PADA PEMILIHAN AUDITOR EKSTERNAL - Dian Fitriyani, Ni Made; Adi Erawati, Ni Made (E-Jurnal Akuntansi, 2016)
External auditor selection is a selection process of choosing external auditor provide audit service. Companies need to attention to the factors that influenc the external auditor selection, in order to obtain a high quality auditor. This study examines whether there is effect of good corporate governance and firm characteristics to external auditor selection. This study conducted at the companies listed on the Indonesia Stock Exchange and follow the Corporate Governance Perception Index (CGPI) for 2011-2013. Sampling by a purposive sampling method. The total sample was 45. Dependent variable is external auditor selection. While the independent variabel is GCG, firm size, profitability, and leverage.  Hypotheses were tested used is logistic regression analysis. It can be concluded from this study is GCG and firm size not significant positif affect on external auditor selection. Profitability significant positif affect on external auditor selection. Leverage not significant negative affect on external auditor selection.
Keywords: good corporate governance, firm characteristics, external auditor selection